2010
DOI: 10.1590/s1677-55382010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal versus extraperitoneal laparoscopic radical prostatectomy during the learning curve: does the surgical approach affect the complication rate?

Abstract: Purpose: To compare the perioperative complication rate obtained with the transperitoneal laparoscopic radical prostatectomy (TLRP) and with the extraperitoneal LRP (ELRP) during the learning curve (LC). Materials and Methods: Data of the initial 40 TLRP (Group 1) were retrospectively compared with the initial 40 ELRP (Group 2). Each Group of patients was operated by two different surgeons. Results: The overall surgical time (175 min x 267.6 min; p < 0.001) and estimated blood loss (177.5 mL x 292.4 mL; p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…2 ). However, after excluding the results from Siqueira et al 17 , sensitivity analysis showed that there was a statistically significant difference between the TLRP and ELRP groups (MD: 30.75; 95% CI: 9.66–51.84; P = 0.004).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…2 ). However, after excluding the results from Siqueira et al 17 , sensitivity analysis showed that there was a statistically significant difference between the TLRP and ELRP groups (MD: 30.75; 95% CI: 9.66–51.84; P = 0.004).…”
Section: Resultsmentioning
confidence: 91%
“…A total of 1715 patients were included in the 14 studies 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ; of these, 939 underwent TLRP and 776 underwent ELRP. All included studies reported on the number of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Siqueira Jr. et al evaluating the complication of the two approaches during the learning curve (initial 40 cases for each approach), did not reveal any differences in overall complication rates. Yet complications encountered during the transperitoneal approach were judged as more serious due to the potential chance of intraperitoneal peritonitis not observed with the extraperitoneal approach [15]. …”
Section: Outcomes Of Lerpmentioning
confidence: 99%
“…Extraperitoneal approach consists of accidental thermal injuries quite uncommon due to peritoneal sequestering of bowels outside the operating field. Moreover, bowel injuries, rarely occurring during trocar insertion and dorsal dissection of the overlying rectum prostatic apex, are considered a less severe complication in the extraperitoneal access than the transperitoneal approach, since the risk of generalized peritonitis is diminished [15]. Urinary bladder injury is mostly encountered during the initial dissection of the extraperitoneal space.…”
Section: Complication Management In Lerpmentioning
confidence: 99%